2009
DOI: 10.1080/00048670802653356
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Change in an Inpatient Anorexia Nervosa Population and Implications for Treatment

Abstract: Motivation is an important predictor of change in anorexia nervosa and preliminary evidence is provided that motivation can be improved in this population. Further investigations, however, of ways of improving motivation in this population need to be conducted, along with the impact of motivational changes on treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
3
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 23 publications
6
130
3
10
Order By: Relevance
“…Of the three studies that did not report significant changes, Weiss et al 28 reported no change in either group, and two studies 17,18 reported non-significant increases in readiness to change. Interestingly, Dean et al 18 found that the non-significant increase was only maintained in the treatment group at follow-up.…”
Section: Readiness To Changementioning
confidence: 99%
See 3 more Smart Citations
“…Of the three studies that did not report significant changes, Weiss et al 28 reported no change in either group, and two studies 17,18 reported non-significant increases in readiness to change. Interestingly, Dean et al 18 found that the non-significant increase was only maintained in the treatment group at follow-up.…”
Section: Readiness To Changementioning
confidence: 99%
“…Allen et al 11 reported a significant decrease, and Wade et al 17 reported a non-significant decrease, in eating pathology in both treatment and comparison groups (at post-treatment and two-week followup, respectively). Interestingly, the decrease found in the Wade et al 17 study continued in the treatment group whereas it increased in the control group between two-and six-week followup. Bulimia Nervosa: Two studies measured the efficacy of MFT 11 and MET 27 on BN.…”
Section: Readiness To Changementioning
confidence: 99%
See 2 more Smart Citations
“…Frequently, the incentive to undergo treatment also comes from friends or colleagues. 8,[10][11][12] Another difficulty in running therapy with patients suffering from AN is the their lack of interest in changing, which results from their perception of their personal health as desirable. Girls and young women often reject any change to their weight or eating habits, even though they may have expressed their consent to therapy.…”
Section: Difficulties In Treating Anorexia Nervosamentioning
confidence: 99%